Mucinous Adenocarcinoma of the Suprapubic Cystostomy Tract without Bladder Involvement - Libo, Man; Gui-zhong, Li (Urology Journal, 2017)
We present a case of adenocarcinoma developing at the vesicocutaneous edge of a vesicostomy, 8 years after it was created, in a patient who had neurogenic bladder secondary to medullitis. The patient died 6 months after the start of surgery therapy. Although transitional and squamous cell carcinoma of a vesicostomy have been reported, to our knowledge, the presence of adenocarcinoma at the vesicostomy edge without bladder involvement has not been reported previously.